ANALISA PENGUATAN STRUKTUR PENAMBAHAN LANTAI BANGUNAN GEDUNG (STUDI KASUS DI DPMPTSP KAB. KUDUS) - Alim Muhroni (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2024)
The research was conducted in the Kudus Regency Public Services building which originally had a floor area of 1172 m2. In 2022 there will be development, so a new floor will need to be added. Where the land area cannot be used to build horizontally, add vertical floors to a 2-story building to become 3 floors. The research was carried out by testing the quality of concrete using the Hammer Test, obtaining a result of 20.75 MPa, then modeling analysis was carried out using SAP 2000 v14 software and manual calculations based on SNI 03-2847-2002, SNI 031726-2012, and SNI 1729-2015. This analysis was carried out in 3 stages, the first was an analysis of the initial conditions of the existing building, the second was an analysis of the existing structure with the additional load of the new floor, and the third analysis was with the additional load and structural strengthening. The results of the structural analysis stages 1 and 2 stated that the beam structural elements experienced overstrength (O/S) or could not withstand the additional load of the 3rd floor. With this data, structural reinforcement calculations were carried out using the concrete jacketing method with a number of longitudinal reinforcement 7D16 stirrups Ø10-100 for beams and the amount of longitudinal reinforcement 8D19 stirrups Ø10-100 and the method of strengthening with steel profile IWF 200.200.8.12.